Listen to the moon - Morpurgo, Michael (New York : Feiwel and Friends, 2015)
May, 1915. Alfie and his fisherman father find a girl on an uninhabited island in the Scillies-- injured, thirsty, lost-- and with absolutely no memory of who she is, or how she came to be there. She can say only one word: Lucy. Is she a mermaid, the victim of a German U-boat, or even, as some islanders suggest, a German spy? Only one thing is for sure: she loves music and moonlight, and it is when she listens to the gramophone that the glimmers of the girl she once was begin to appear.--
Accelerated Reader
Keywords: World War, 1914-1918 -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Shipwreck survival -- Juvenile fiction; Shipwreck survival -- Fiction; Historical fiction; Historical fiction; Historical fiction -- Juvenile; Historical fiction -- Young adult